Balancing livelihood enhancement and ecosystem conservation in seaweed farmed areas: A case study from Gulf of Mannar Biosphere Reserve, India. (15th June 2021) - Krishnan, P.; Abhilash, K.R.; Sreeraj, C.R.; Samuel, V. Deepak; Purvaja, R.; Anand, A.; Mahapatra, M.; Sankar, R.; Raghuraman, R.; Ramesh, R.
Abstract: Kappaphycus alvarezii, a red seaweed cultured in tropical waters for extraction of carrageenan, is widely considered a bioinvader of coral reefs. In India, this seaweed is cultivated in Palk Bay, South India by the coastal community amidst the concern of its invasion in the sub-tidal reef regions of adjoining Gulf of Mannar Marine National Park (GoMMNP). The current study was undertaken to assess the extent of coral reefs in Pak Bay and Gulf of Mannar (GoM) affected by this red alga and evaluate the possible causes for its spread in GoM including the long-term commercial seaweed cultivation in Palk Bay. The study was carried out in Palk Bay and 19 emergent and two submerged Islands of GoM. Landsat 7 Enhanced Thematic Mapper Plus (ETM+) satellite images were used to map the spatial cover of the alga over the reef. The reef zones with K. alvarezii were mapped using GIS. The study showed that K. alvarezii has not spread over the coral reefs in Palk Bay, a region where the cultivation is underway for over ten years. Nevertheless, the algae had spread in some of the islands in Gulf of Mannar region viz ., Shingle (1.1 ha; 2.12% of reef area), Krusadai (0.572 ha; 0.35% of reef area) and Mulli Islands (0.00025 ha; 0.00022% of reef area). The temporal change in the extent of live corals (between 2002 and 2014) in Palk Bay and GoM corroborated a possible phase shift i.e., from a coral dominated reef to an algal dominated reef, with Halimeda spp., Caulerpa spp. and Ulva reticulata being the dominant macro-algae. Based on a critical analysis of the sources of fragments for the spread of the alga in GoM and the factors that aid in their dispersion, we conclude that K. alvarezii farming activities in Palk Bay are not the primary source for the broken fragments, responsible for the spread of the alga in GoM. However, considering the potential risks of unintended transfer of farmed algae into the sensitive ecosystems, the study calls for evolving codes for cultivation of seaweeds so as to leave least ecological footprints over the coastal ecologically sensitive ecosystems like coral reefs. HIGHLIGHTS: Kappaphycus alvarezii has not spread over the coral reefs in Palk Bay, where it has been cultivated for over ten years. The spread of K. alvarezii patches over the reefs of Gulf of Mannar cannot be attributed to their farming in Palk Bay. Codes of cultivation with strategies to mitigate invasion must be evolved to reduce ecological footprint of Kappaphycus .